Low Skilled Workforce in the U.S.: Key findings from the Program for International Assessment of Adult Competencies (PIAAC) - Emily Pawlowski (Adult Education Research Conference, 2015)
This paper provides an overview of the Program for International Assessment of Adult Competencies (PIAAC), a large-scale international assessment of adult skills. Results on the literacy, numeracy, and digital problem solving skills of the low-skilled U.S. workforce will also be presented.
Keywords: adult literacy; adult skills; workforce; international comparison